Molecular detection of Grapevine fanleaf Virus by the isolation of ssRNA and dsRNA from Xiphinema index - Delpasand Khabbazi, Afsasneh; Bashir, Nemat Sokhandan; Asl, Ebrahim Zahedi; Delpasand Khabbazi, Saber (Journal of Scientific Agriculture, 2017)
Xiphinema index is an important grapevine pathogen nematode which also vectors Grapevine fanleaf virus. The viral genes involved in transmission by the vector nematode are mapped to the C-terminal residues of RNA2-encoded polyprotein. To recognize viruliferous nematodes, there are some serological and molecular methods. In this study, we extract RNA and dsRNA of the virus, then Reverse transcription-polymerase Chain Reaction was done with virus specific primers to detect virus in its vector. The virus was detected by visualizing the desired 350 and 750 bp gene fragments in electrophoresis. This study reduces the virus detection time to only couple of hours with least imposed charges, and could be employed in transmission experiments as well.